(untitled) (Cadernos de Sociomuseologia, 2017)
The present volume of Journal of Sociomuseology addresses several essential questions for the deepening of a Museology that aims to act in favor of Human Rights. These are articles present different dialogues that are established between memory, human rights, respect for difference, social representations, community involvement, material and immaterial culture. In each article we feel a sensitivity also made of different life paths. In fact, for decades, Museology has been renewed, trying to be attentive to the contemporary world. Years of resistance as well as conviction are now expressed in the Recommendation on the protection and promotion of museums and collections, their diversity and their role in society, announced by UNESCO in November 2015. In this important document it is quite explicit that the social function of museums is, or should be, the deepest reason for their existence, as intended by the Santiago Declaration of 1972, or the objectives to be attained when the MINOM was created in 1985. A renewal of Museology which, since 1991, has shaped the work of our Department in which New Museology, Social Museology, Altermuseology, Public Museology and Sociomuseology express an understanding of Museology as part of the field of Social Sciences at the service of Dignity Human.